CULTURAL CONTENTS IN SPEAKING MATERIALS AND ACTIVITIES FOR TENTH-GRADERS - Nur Lailatus Sholihah; Rohmani Nur Indah (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
EFL textbooks should be valued based on their visual illustration and based on their cultural background and goals of EFL learning. The study aimed to report the results of a textbook analysis to identify which type of culture and what themes of culture were introduced in the tenth graders of Indonesian senior high school. Theory of cultures proposed by Cortazzi Jin (1999) and Chen Lee (2004) were adapted for examining specific aspects of culture under formal culture and aspects of life culture. The analysis revealed that the percentage of source culture (45,7%) and unidentified culture (42,9%) is the same in the textbook. The textbook was dominated by source culture content among identified cultural content, while international culture (5,7%) and target culture (5,7%) contained a small percentage. It was also found out that among the 19 cultural themes under formal culture and aspects of life culture, the researcher found four themes such as lifestyle, gestures, and holiday under aspects of life culture and only history under formal culture. The predominant theme was aspects of life culture of lifestyle.